2006
DOI: 10.3354/meps323021
|View full text |Cite
|
Sign up to set email alerts
|

Changing bacterioplankton growth characteristics on a large spatial scale: oligotrophic versus mesotrophic ocean

Abstract: This study deals with large spatial scale differences in the ratios between bacterial leucine incorporation (TLi: protein synthesis) and thymidine incorporation (TTi: DNA synthesis) in oligotrophic offshore and comparatively more mesotrophic inshore (sub)tropical regions of the Atlantic Ocean. Observations were derived from 2 RV 'Polarstern' cruises, one of which traversed a meridional mid-ocean transect while the other followed the African coast line. Average values (from 42°N to 35°S) of TLi, TTi and chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
6
16
0
Order By: Relevance
“…Lemée et al (2002) reported a wide range (1-44%) in BGE in one oligotrophic Mediterranean station during the year, with an overall average of 11%, similar to our overall average of 13%, and a similar range was reported by Reinthaler and Herndl (2005) for the North Sea. The molar ratio of leucine to thymidine incorporation has been shown to vary widely between systems (Chin-Leo and Kirchman 1990; Gasol et al 1998;Hoppe et al 2006) and also within a sample with time (Sherr et al 1999), and our results are within the range reported. This variability has been interpreted as reflecting various degrees of uncoupling between protein and nucleic acid synthesis (Chin-Leo and Kirchman 1990;Torreton and Dufour 1996;Sherr et al 2001), although Hoppe et al (2006) have argued that the absolute values of the ratio that are associated with balanced growth probably differ between communities and regions.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Lemée et al (2002) reported a wide range (1-44%) in BGE in one oligotrophic Mediterranean station during the year, with an overall average of 11%, similar to our overall average of 13%, and a similar range was reported by Reinthaler and Herndl (2005) for the North Sea. The molar ratio of leucine to thymidine incorporation has been shown to vary widely between systems (Chin-Leo and Kirchman 1990; Gasol et al 1998;Hoppe et al 2006) and also within a sample with time (Sherr et al 1999), and our results are within the range reported. This variability has been interpreted as reflecting various degrees of uncoupling between protein and nucleic acid synthesis (Chin-Leo and Kirchman 1990;Torreton and Dufour 1996;Sherr et al 2001), although Hoppe et al (2006) have argued that the absolute values of the ratio that are associated with balanced growth probably differ between communities and regions.…”
Section: Discussionsupporting
confidence: 79%
“…The molar ratio of leucine to thymidine incorporation has been shown to vary widely between systems (Chin-Leo and Kirchman 1990; Gasol et al 1998;Hoppe et al 2006) and also within a sample with time (Sherr et al 1999), and our results are within the range reported. This variability has been interpreted as reflecting various degrees of uncoupling between protein and nucleic acid synthesis (Chin-Leo and Kirchman 1990;Torreton and Dufour 1996;Sherr et al 2001), although Hoppe et al (2006) have argued that the absolute values of the ratio that are associated with balanced growth probably differ between communities and regions. The range of values observed for the various metabolic variables was comparable between the surface and pycnocline layers, although their spatial patterns were often quite different, probably reflecting the characteristics of the water masses that coexist vertically along the transect.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In our study, we observed a decreased role for protein in cell surface reactivity, and increased role for carbohydrates and lipids, as media N:P ratios departed from the reference condition of 14.5. This appears to mirror observations from the marine realm, where gross protein production by bacterioplankton (as measured by leucine incorporation) has been observed to decrease from oligotrophic offshore settings (where it is maximal) to mesotrophic near-shore settings (e.g., in the sub-tropical Atlantic ocean; Hoppe et al, 2006). Our finding that shifts in nutrient and growth regimes yields important surface compositional modifications is consistent with the emerging view of compositional plasticity amongst marine cyanobacteria, and crucially, constitutes the first evidence that such modifications may be expressed in the physico-chemical properties of the cyanobacterial cell surface -and thus in it's capacity to sequester metals from marine waters by adsorption and co-precipitation processes.…”
Section: .Discussionmentioning
confidence: 66%
“…The work of Massana et al (2001), showing the microbial growth in Antarctic waters is an example of this. Hoppe et al (2006) considered that substrate supply is more important than temperature in the regulation of microbial growth on a large spatial scale. Troncoso et al (2003) also reported that substrate availability seems to be more important than temperature in determining microbial activity and abundance in the Humboldt Current System.…”
Section: Discussionmentioning
confidence: 99%